On the estimation of panel fiscal reaction functions: Heterogeneity or fiscal fatigue? - Gerdie Everaert; Stijn Jansen (National Bank of Belgium, 2017)
This paper investigates whether fiscal fatigue is a robust characteristic of the fiscal reaction function in a panel of OECD countries over the period 1970-2014 or merely an artifact of ignoring important aspects of the panel dimension of the data. More specifically, we test whether the quadratic and cubic debt-to-GDP terms remain significant once dynamics, heterogeneous slopes and an asymmetric reaction to the business cycle are allowed for. The results show a significant heterogeneous reaction of the primary balance to lagged debt with fiscal fatigue not being a general characteristic of the fiscal reaction function shared by all countries in our panel. In line with the literature, we further find that fiscal balances tend to deteriorate in contractions without correspondingly improving during expansions. Explorative stochastic debt simulations show that debt forecasts crucially depend on the specification of the fiscal reaction function.
Keywords: E62; H62; H63; H68; 330; Fiscal reaction function; dynamics; non-linearities; fiscal fatigue; debt sustainability analysis